A review of surface functionalisation of diamond for thermionic emission applications. (January 2021) - James, Michael C.; Fogarty, Fabian; Zulkharnay, Ramiz; Fox, Neil A.; May, Paul W.
Abstract: Surface functionalisation of diamond can produce negative electron affinity (NEA), where the conduction band lies higher in energy than the vacuum level. Hydrogen termination is well-known to produce NEA on diamond but can be removed by temperatures above ∼700 °C, making it unsuitable for diamond-based thermionic applications, where high temperatures are converted into electricity via an electron emission process. In this review article we give an overview of thermionic emission, describe the potential applications of diamond-based thermionic energy converters, then review the different surface termination schemes that can provide a diamond surface with NEA. We discuss the relative merits of the different NEA surfaces that have been developed both computationally and experimentally as alternative cathode materials for thermionic devices. Graphical abstract: Image 1